South Africa: Agricultural R&D Indicators Factsheet - Beintema, Nienke M.; Gao, Lang; Chaminuka, Petronella (Agricultural Research Council (ARC) of South Africa, 2017)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also features a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.